A COMPARISON OF THE TRADITIONAL (WESTERN STYLE) BANK AND ISLAMIC BANK MODELS - Adnan, Muhammad A; Gaffikin, M.J.R (JURNAL BISNIS STRATEGI, 1998)
There has been a remarkable increase  in the number  Islamic banks and Islamic  Financial  Institution since  the  1970s.   There are  about a hundred Islamic Banks and Financial Institutions currently in the world. It is useful and interesting to know how Islamic banks  differ from  the  Western (Traditional)  style  bank?This paper surveys the  differences  between  the twostyle  of bank. A comparison is made  of the origin of each style of bank.  their development,  the types of products and services  they  offer:  their organization and their financial statements.The paper concludes that the basic  difference  is in the  treatment  of interest.  But this in tum generates some other differences.  Interestingly, in the sense  of accounting concepts and practices,   it  seems that   both styles are  not significantly different.However. a close examination of this seems  to be interesting and is the focus  of study,  because  each  style  of bank  has  developed with  different perspective.